2000
DOI: 10.1046/j.1440-1711.2000.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise effects on systemic immunity

Abstract: Summary Heavy exertion has acute and chronic influences on systemic immunity. In the resting state, the immune systems of athletes and non-athletes are more similar than disparate with the exception of NK cell activity, which tends to be elevated in athletes. Many components of the immune system exhibit adverse change after prolonged, heavy exertion. These immune changes occur in several compartments of the immune system and body (e.g. the skin, upper respiratory tract mucosal tissue, lung, blood and muscle). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 48 publications
(19 reference statements)
2
38
0
6
Order By: Relevance
“…A leucocitose se dá, em um primeiro momento, pelo aumento do número de neutrófilos, com a função de remover do tecido elementos indesejáveis relacionados à lesão tecidual por fagocitose (da Silva & Macedo, 2011), corroborando com Nieman (2000) ao apontar uma elevação da concentração de leucócitos após a realização de um exercício de corrida ou de bicicleta a aproximadamente 75% da capacidade aeróbica máxima. Segundo Rosa…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A leucocitose se dá, em um primeiro momento, pelo aumento do número de neutrófilos, com a função de remover do tecido elementos indesejáveis relacionados à lesão tecidual por fagocitose (da Silva & Macedo, 2011), corroborando com Nieman (2000) ao apontar uma elevação da concentração de leucócitos após a realização de um exercício de corrida ou de bicicleta a aproximadamente 75% da capacidade aeróbica máxima. Segundo Rosa…”
Section: Resultsunclassified
“…As alterações agudas no sistema imune estão relacionadas à ação dos hormônios como as catecolaminas, cortisol, hormônio adrenocorticotrófico (ACTH), insulina, glucagon, hormônio o crescimento (GH) e vasopressina (da Silva & Macedo, 2011;Nieman, 2000;Rosa & Vaisberg, 2002). Elevadas concentrações de catecolaminas, por exemplo, promovem um incremento da concentração leucocitária através da redução da adesão dos leucócitos ao endotélio vascular e pela maior liberação pelos órgãos linfoides (Cardia et al, 2006).…”
Section: Resposta Hematológica Ao Teste Máximo | 43unclassified
See 1 more Smart Citation
“…Research has shown that physical activity may cause alterations in concentration, proportion and function of blood white cells, especially in the nuclear polymorphous leukocytes, in the natural-killer cells, and in the lymphocytes, affecting also the immunoglobulins, besides other factors 19 . Cortisol and catecholamine, besides active metabolites, also cause leukocyte redistribution, determining an immunosuppression activity 20 . Despite being widely discussed, some scientists mention the existence of an 'open window' in a period of three to 72 hours after exercise practice, when virus and bacteria would have easier access to the organism, a fact which could be increased with poor nutrition and decrease of hours of sleep 21 .…”
Section: Introductionmentioning
confidence: 99%
“…O sistema imunológico é formado por estruturas individualizadas, que incluem os órgãos linfóides primários como a medula óssea e o timo, os quais produzem os componentes celulares do sistema imunológicos como linfócitos, macrófagos e órgãos linfóides secundários onde encontramos os linfonodos, baço, tonsilas e placas de Peyer (GLEESON, 2000;NIEMAN;CHINEN e SHEARER, 2004).…”
Section: Desnutrição E Sistema Imunológicounclassified